The other Americans [book club bag] - Lalami, Laila, 1968- (Pantheon Books, 2019)
Late one spring night, Driss Guerraoui, a Moroccan immigrant in California, is walking across a darkened intersection when he is killed by a speeding car. The repercussions of his death bring together a diverse cast of characters: Guerraoui's daughter Nora, a jazz composer who returns to the small town in the Mojave she thought she'd left for good; his widow Maryam, who still pines after her life in the old country; Efrain, an undocumented witness whose fear of deportation prevents him from coming forward; Jeremy, a former classmate of Nora's and a veteran of the Iraq war; Coleman, a detective who is slowly discovering her son's secrets; Anderson, a neighbor trying to reconnect with his family; and the murdered man himself. As the characters tell their stories, the invisible connections that tie them together--even while they remain deeply divided by race, religion, or class--are slowly revealed. When the mystery of what happened to Driss Guerraoui unfolds, a family's secrets are exposed, a town's hypocrisies are faced, and love, in its messy and unpredictable forms, is born.